PELAKSANAAN PENILAIAN AUTENTIK PEMBELAJARAN EKONOMI BERDASARKAN KURIKULUM 2013 DI SMA SANTO FRANSISKUS ASISI PONTIANAK - Susiana, Susiana; Buwono, Sri; Warneri, Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this study was to determine the implementation of authentic assessment of economic learning based on curriculum 2013 at SMA Santo Fransiskus Asisi Pontianak. The method used in this research was descriptive in form of research survey. The soerces of data in this research were the economic’s teacher of class X, XI, and XII IPS, WK Kurikulum of SMA Santo Fransiskus Asisi and documents relating to the implementation of authentic assessment namely learning tools such as lesson plan, syllabus, student worksheet, and the media of learning. Tools of data colection used in this research were observation sheet, interview, and documentation. Techniques of data analysis used in this research was data reduction, data presentation, and conclusions drawing, then the validity of the data is examined using triangulation technique. The researcher conducted this reseach for seven days, by doing the observation in six times (four days) and the interview in three times (three days). The result of this research showed that the implementation of authentic assessment on the attitude, knowledge and skill competency of the economic’s teacher were categorized as not effective yet. Keywords: The Implementation of Authentic Assessment, Economic Learning, Curriculum 2013